Kebijakan Logistik Maritim Indonesia: Perluasan Pasar Regional dan Penanganan Hambatan Non-Tarif di Asia Tenggara (2020–2024) - Rieke Clara Mustikasari; Jhon Pattinussa; Roy Pratikno (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2026)
This study examines Indonesia’s maritime logistics policy during 2020–2024 and its role in facilitating market expansion and reducing non-tariff barriers (NTBs) within the Association of Southeast Asian Nations (ASEAN). As the world’s largest archipelagic state, Indonesia relies heavily on maritime transport, yet high logistics costs, estimated at 20–24 percent of total production costs, and persistent NTBs continue to constrain export competitiveness. Using descriptive and comparative methods, this research evaluates Indonesia’s strategy through institutional reforms, infrastructure modernization, and regional cooperation mechanisms, while benchmarking performance against Singapore, Malaysia, and Thailand using indicators such as port efficiency, digital integration, and the Logistics Performance Index (LPI). The findings indicate measurable progress through customs digitalization under the National Single Window (NSW), implementation of the National Logistics Ecosystem (NLE), and participation in regional frameworks, including the ASEAN Single Window (ASW) and the ASEAN Customs Transit System (ACTS). These initiatives have reduced dwelling time, improved supply-chain predictability, and supported trade growth, with Indonesia’s total trade value increasing from USD 304.76 billion in 2020 to USD 529.35 billion in 2022. Nevertheless, significant challenges remain, including regulatory fragmentation, uneven port development, limited digital interoperability, and inconsistent institutional capacity across regions. The study concludes that maritime logistics reforms have strengthened Indonesia’s integration into ASEAN trade networks; however, sustained competitiveness will require deeper regulatory harmonization, systematic performance measurement, infrastructure equalization, and long-term bureaucratic modernization to effectively mitigate NTBs and secure durable market expansion.